Risk factors of speech and language disorders in children - Rusli, Vinia; Suryawan, Ahmad; Irmawati, Mira; Irwanto, Irwanto; Notobroto, Hari Basuki (Paediatrica Indonesiana, 2024)
Background Speech and language problems are developmental disorders often observed in children. Risk factors for speech and language disorders can occur prenatally, perinatally, or postnatally. Recognizing the risk factors for speech and language problems is essential for early diagnosis and intervention. Objective To identify risk and protective factors of speech and language disorders in children. Methods This case-control study was conducted in the Growth and Development Clinic at Dr. Soetomo Hospital, Siloam Hospital, Kendangsari Merr Hospital, and Darmo Hospital, Surabaya, East Java. Subjects with normal development were included in the control group, subjects with speech-language development disorders with no additional problems were included in the primary case group, and subjects with speech-language disorders and additional problems were included in the secondary case group. Subjects underwent history-taking and developmental examinations to assess for risk factors and types of speech-language disorders. Results During March – July 2023, 162 subjects aged 2-6 years met the inclusion criteria. The significant risk factors in the primary group were male sex (P=0.000), age 2-3 years (P=0.01), and maternal age 19-35 years (P=0.018). The protective factor identified was not bilingual (P=0.046). In the secondary group, the significant risk factor was male gender (P=0.002). The protective factors obtained were absence of seizures (P=0.028) and not being bilingual (P=0.045). Conclusion Male gender is a risk factor while non-bilingual is protective for speech-language disorders in children.